Effect of structural modification in the amine portion of substituted aminobutyl-benzamides as ligands for binding σ(1) and σ(2) receptors - Fan, Kuo-Hsien (2011)
5-Bromo-N-[4-(6,7-dimethoxy-3,4-dihydro-1H-isoquinolin-2-yl)-butyl)]-2,3-dimethoxybenzamide (1) is one of the most potent and selective σ(2) receptor ligands reported to date. A series of new analogs, where the amine ring fused to the aromatic ring was varied in size (5 - 7) and the location of the nitrogen in this ring was modified, has been synthesized and assessed for their σ(1) / σ(2) binding affinity and selectivity. The binding affinity of an open-chained variant of 1 was also evaluated. Only the 5-membered ring congener of 1 displayed a higher σ(1) / σ(2) selectivity, derived from a higher σ(2) affinity and a lower σ(1) affinity. Positioning the nitrogen adjacent to the aromatic ring in the 5-membered and 6-membered ring congeners dramatically decreased affinity for both subtypes. Thus, location of the nitrogen within a constrained ring is confirmed to be key to the exceptional σ(2) receptor binding affinity and selectivity for this active series.